PELAKSANAAN PERJANJIAN KERJA WAKTU TERTENTU DI PT KIMIA FARMA BERDASARKAN UNDANG-UNDANG CIPTA KERJA - Yuli Rahmadani Azis (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTPT. Kimia Farma made a collective work agreement with non-permanent workers, one of which contained the contents of the agreement regarding the appointment of non-permanent workers to become permanent workers on the condition that the temporary workers must work at PT. Pharmaceutical Chemistry.Law Number 13 of 2003 concerning Manpower as amended through Law Number 11 of 2020 concerning Job Creation, one of which is regarding employment relations based on a certain time work agreement (also known as PKWT). In practice in the field, there are often problems related to the rights of PKWT workers, one of which is special requirements, especially related to the duration of the agreement and the type of work agreed. Whether things like this in the provisions of the Job Creation Act have been carried out by the Company or not. The type of research used is empirical juridical research, research using field data.The results showed that a certain time work agreement at PT. Kimia Farma based on the Manpower Act has special requirements, especially related to the term of the agreement and the type of work that is agreed upon. The term of a work agreement for a certain time can only be made for a maximum of two years, it can only be extended once for a maximum period of one year, or it can be renewed a maximum of once for a maximum of two years. As for the type of work itself, not all jobs can be used as objects of a certain time work agreement, but only certain jobs. Keywords: PKWT, Employment Agreement, Job Creation Act